HUBUNGAN KOMUNIKASI ORANGTUA TERHADAP PERILAKU SEKS BEBAS PADA REMAJA DI SMA NEGERI 5 PEMATANG SIANTAR - Raden Roro Siti Hatati Surjantini (Majalah Ilmiah METHODA, 2018)
Family conflicts often occur due to lack of communication between parents and children. Parents who are equally busy cause the intensity and quality of communication to be very lacking and often lead to disputes. Through communication, parents should be the main source of information and educators about free sex in their teens. Based on the initial survey conducted, it was found that around 60% did not have free sex. This situation is related to good communication between parents and children, especially communication about sex and good sex education from parents to children who have already obtained children from parents. This study aims to analyze the relationship of parental communication (openness, empathy, supportive attitude, positive attitude and equality) to free sex behavior in adolescents in Pematangsiantar 5 SMA. This type of research is an analytical survey with a cross sectional approach. The population of 160 people sampled was 20 people, taken by cluster sampling technique. Data were obtained using a questionnaire, analyzed by the chi square test at α = 5%. Conclusions that parents and children are expected to maintain joint communication of free sex behavior of Pematangsiantar 5 High School students, to students of Pematangsiantar State Senior High School 5 to always improve self-control and be able to withstand desires or momentary drives that conflict with inappropriate behavior with social norms and to the State High School 5 Pematangsiantar still pay attention to students / i and direct students to not engage in free sex.